Factor affecting variation orders on mosque construction in Perak / Nor Suhada Zulkifli and Nur’ain Ismail - Zulkifli, Nor Suhada; Ismail, Nur’ain (2023)
The mosque symbolizes the fundamental aspects of Islamic thought throughout the Muslim world. Therefore, the construction of mosques in this country increases over time. As a postcolonial nation, Malaysia's mosques have incorporated a variety of architectural styles and serve as a visual representation of the nation's multicultural population. However, with varying styles of architecture, most of the mosque construction projects in Perak had undergone many variation orders, which increased client expenditures beyond the planned budget. Hence, the objective of this research was to identify the factors affecting variation orders on mosque construction in Perak. This research conducted based on a thorough review of the literature review and qualitative method by case studies on three (3) mosques construction in Perak. The findings showed that the recurrent factors all the mosque construction in Perak have undergone variation because of the changes of scope, changes in specification, changes in design by consultant, changes in schedule, and impediment to prompt decision making process. Addressing these factors is crucial for efficient and cost-effective mosque construction projects in the future. By understanding and managing these challenges, stakeholders can ensure the successful realization of mosques that symbolize the cultural and religious significance within Malaysia and uphold its diverse heritage.